Community Structure of Mollusca (Gastropoda and Bivalvia) at Toronipa Beach - Suluwi , Hamsir; Afu , La Ode Alirman; Rahmadani (Jurnal Biologi Tropis, 2024)
Toronipa Beach is known to have high biodiversity, especially in the Mollusca community such as Gastropoda and Bivalvia. However, research on the distribution and abundance of Mollusca species in this area, especially related to environmental changes, is still limited. To fill this gap, an analysis study was conducted on the structure of the Toronipa Beach Mollusca community as a basis for effective conservation efforts. Data were collected through purposive sampling methods at three different locations, then analyzed using the Shannon-Wiener Index method, evenness index, and dominance index. The results showed that the North of Toronipa Beach had the highest diversity with a Simpson index of 0.91, followed by the West with 0.76, and the East with 0.75. These differences in diversity reflect variations in microhabitats, such as substrates, water flow, and human activities, which affect the distribution and abundance of species. This study highlights the importance of proper management and conservation to maintain biodiversity in Toronipa Beach and provides a basis for further studies on the impacts of the environment and climate change on coastal ecosystems.